G20 Delhi summit consensus: internationalism of India and China - Suryanarayana, Pisupati Sadasiva (2023)
Notwithstanding their bilateral economic disputes, armed clashes along their frontier territories, and geostrategic rivalry, China and India have surprisingly cooperated in facing a polarised geopolitical ambience during the G20 summit in Delhi on 9-10 September 2023. China supported India’s leadership in reaching a G20 consensus on the Ukraine crisis and the development priorities of the global south.